(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
It is usually assumed that between the 16th and the 18th centuries language sciences included three main research lines: works on language origin; practical grammars and philosophical grammars. This view has been countered by Alfieri (2019), who showed that between the 13th and the 16th centuries philosophical grammars comprised two types of works which were substantially different as for their settlement on the time axis, as well as for their theory of derivatio. In this case the hypothesis in Alfieri (2019) will be taken up, showing that also in the 17th and 18th centuries philosophical grammars included two groups of works: a-chronic grammars that exclude data on word-formation; pan-chronic grammars that describe data on word-formation with special attention, but interpret these data only sub specie originis linguae. KEYWORDS: History of linguistics, word-formation, rational grammars, philosophical grammars, synchrony and diachrony.